Parasocial relationship influence on the upcycled fashion purchase intention among igeneration in Malaysia post-Covid-19: an empirical study - Nornajihah Nadia Hasbullah; Ag Kaifah Riyard Kiflee; Mastura roni; Nur hafidzah idris; Irfah Najihah Basir Malan; Olakunle Jayeola; Muhammad Fairuz Jamil; Ahmad Fadhly Arham (Journal of Theoretical and Applied Information Technology (Jatit), 2022)
The coronavirus disease (COVID-19) pandemic has impacted the pursuit of sustainable development in various ways. Current consumer trends suggest an increased awareness of sustainable consumption or fashion consumption. Past studies have focused more on general concepts of sustainable fashion consumption (SFC), including environmental, ethical, second-hand, and recycling while neglecting upcycling fashion. Therefore, the study investigated the Malaysian iGeneration purchase intention of upcycled fashion products postCOVID-19. The study extended the moderating role of parasocial relationship based on the Theory Planned Behaviour (TPB). A quantitative online survey was conducted among 230 respondents from IGeneration between 10 to 25 years old in Malaysia. The hypotheses were tested using Partial Least Squares Structural Equation Modelling (PLS-SEM). The study outcomes exhibited empirical support for the proposed research model. Two out of six hypothesized relationships were accepted. Specifically, subjective norm was positively linked to the purchase intention of upcycled fashion products. Meanwhile, parasocial relationship moderated subjective norm and purchase intention. The study provided insights into the application of TPB-based framework and enhanced knowledge of fashion industry players, educators and communities.